Pengaruh Debt to Equity Ratio (DER) dan Return on Equity (ROE) Terhadap Nilai Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Dika Ria Utami; Wulan Rezky Amalya (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to test and analyze the effect of Debt to Equity Ratio (DER) and Return on Equity (ROE) on the Value of Mining Sector Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The population in this study were 29 mining sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The sample used in this study was a purposive sampling method totaling 33 companies after being multiplied by 3 years of research. The data analysis method in this study was panel data regression analysis with the help of Eviews Software version 10. Based on the results of this study, it shows that partially Debt to Equity Ratio (DER) has a negative and significant effect on the Value of Mining Sector Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Return on Equity (ROE) partially has a positive and significant effect on the Value of Mining Sector Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The results of the study also show that simultaneously the Debt to Equity Ratio (DER) and Return on Equity (ROE) have a significant effect on the Company Value of the mining sector listed on the Indonesia Stock Exchange for the 2019-2021 period.